SIMPUL-SIMPUL PENDIDIKAN DALAM SURAH AL ANFÃL DAN AL TAUBAH - Hidayati, Noorazmah (Jurnal Studia Insania, 2013)
Today, concept of jihad disposed wrong to be understood. Jihad mean as a war, even must destroyed some people and creatures with in the name of Islam. As a consequence Islam refer to a terorist religion. This opinion must be corrected, because Islam is ârahmatan lil âalamiinâ. In fact, in independent time jihad should be manifested to protect equitable and moral of humanbeing. This article describes some essences of education of jihad in surah al AnfÃ¢l and al Taubah with the result that every action will valued as jihad and humanbeing values will protected.